Awareness of and Preparedness for Digital Broadcasting among Communication Practitioners and Educators in Uyo - Obot, Charles; Inwang, Idaresit Idongesit (Athens Journal of Mass Media and Communications (online), 2017)
The digitization of broadcasting is considered one of the most significant developments in the broadcasting industry. Communication practitioners and educators are expected to play key roles in the digitization process. The objectives of the study were; to investigate the level of awareness of the oncoming digitization project among communication educators, to ascertain the level of preparedness of the communication practitioners for the transition to digital broadcasting, to find out the possible implications of full digitization on communication education in Nigeria, to investigate the implications of digital broadcasting on programming and content production, and to find out possible challenges communication educators and practitioners in Uyo would face during digital broadcasting. The population of this study comprised all the communication practitioners in television stations in Uyo, Nigeria who work in the news, programming and engineering departments. Communication educators who teach communication courses in tertiary institutions in Uyo also constituted the population of the study. Communication educators in tertiary institutions and communication practitioners in broadcast stations, especially those in the news, programming and engineering departments in Uyo, Nigeria were considered the most appropriate subjects for the study. The survey method was adopted for this study. The research instrument (questionnaire) was administered directly to the respondents by the researchers. Based on the findings of the study, it is concluded that communication educators in Uyo are aware of the digitization process in the broadcast industry and are already teaching the subject of digitization in tertiary institutions in Uyo, Nigeria in courses including Trends in Media Technology, Information and Communication Technology, among others.